The Role of Intellectual Capital Structure in the Diversification of the Indonesian Banking Sector From 2011-2022 - Sean Michael Gunawan; Valentino Budhidharma (Universitas Pelita Harapan, 2024)
This thesis investigates the impact of intellectual resources on the variety approaches of financial institutions listed on the Indonesian region Stock Exchange from 2011 to 2022, within the Indonesian region's rapidly evolving financial institution sector. Utilizing panel regression analysis and Driscoll-Kraay Standard Errors to address issues like heteroscedasticity and autocorrelation, the analysis finds that structural capital effectiveness enhances asset variety, while higher capital utilized effectiveness leads to reduced income variety, suggesting an optimization of income-generating assets. Additionally, financial leverage correlates with asset variety, indicating strategic debt usage in variety efforts. Interestingly, factors such as financial institution size and competition show no significant impact, reflecting the complex nature of strategic decisions in financial institution. This investigation enriches understanding of how financial institutions in emerging markets use internal efficiencies and strategic choices to navigate market dynamics, offering valuable insights for financial managers on capital structure and variety approaches in competitive environments.